Modern in Venice - Docomomo Journal (Docomomo Journal, 2022)
The 2014 Venice Architecture Biennale is on display from June to November. This year’s edition is directed by Rem Koolhaas and is bringing major novelties. For the first time the event will be held for six months and was assembled for a longer period than ever be- fore. Koolhaas set this new schedule because he was committed to create a research-based exhibition. According to Paolo Baratta, the president of the Venice Biennale, this repre- sents an unprecedented method that had never been used in past editions. The director engaged all participants in the theme Fun- damentals and tried to establish a narrative between the show’s three main components: Absorbing Modernity, Elements of Architecture and Monditalia.